Dust distribution in planetary nebulae - Pignata, Rafael Andrés (2023)
Context. Planetary nebulae (PN) have long been known to consist of gas, molecules and dust. The vast majority of the work in which properties of the dust of these objects are inferred were carried out with infrared observations. The downside with this technique is that infrared emision not only comes from dust. On the other hand, depending on the photometric band in which we are observing we will have information of the dust in a certain temperature range. In this sense, we use a technique that gives information about the dust, without nebular contamination, and regardless of its temperature.Aims. The primary objective is to present an atlas of images with the distribution of dust in planetary nebulae.Methods.We obtaing images in narrow-band filter centred on the nebular emission of the Balmer lines Hα and Hβ. These images were obtained with the moderate-aperture telescopes at the Estación Astrofísica de Bosque Alegre.We propose to combine these images toobtain the distribution of dust in galactic planetary nebulae. This technique allows to infer the distribution of the dust, independent ofits temperature. In addition this photometric data are combined with spetroscopic one, which strengthens our results.Results. We present original images of 29 bright south PN in which shows its dust spatial distribution. The data provided by this atlas represent the most extensive image surveys for PNe.